More to episodic memory than epistemic assertion: The role of social bonds and interpersonal connection. (22nd January 2018) - Hirst, William; Echterhoff, Gerald
Abstract: Remembering is dynamically entangled in conversations. The communicative function of episodic memory can be epistemic, as suggested by Mahr & Csibra (M&C). However, remembering can have genuinely social functions, specifically, the creation or consolidation of interpersonal relationships. Autonoesis, a distinct feature of episodic memory, is more likely to have evolved in the service of social binding than of epistemic assertiveness.